A durable VO2(M)/Zn battery with ultrahigh rate capability enabled by pseudocapacitive proton insertion. Issue 4 (2nd January 2020) - Zhang, Lishang; Miao, Ling; Zhang, Bao; Wang, Jinsong; Liu, Jia; Tan, Qiuyang; Wan, Houzhao; Jiang, Jianjun
Abstract : Reversible hydroxyzinc sulfate hydrate deposition/dissolution in electrochemical process could be observed on cathode surface. Good long term stability retention could also be achieved at high current density of 20 A g −1 . Abstract : Energy storage devices with low-cost and high-safety features are essential because of the continued consumption of fossil fuels. Aqueous zinc ion batteries, owing to their superior safety, high abundance and high theoretic capacity, have attracted increasing attention. Herein, for the first time, the M phase VO2 integrated with carbon nanotubes as a binder-free cathode for zinc ion batteries was studied. The as-prepared binder-free cathode shows ultrahigh rate performance with 248 mA h g −1 at 2 A g −1, 232.6 mA h g −1 (93.8% maintained compared to 2 A g −1 ) at 20 A g −1 and 194.9 mA h g −1 at 40 A g −1 . Good stability was achieved with 84.5% retention after up to 5000 cycles at 20 A g −1 . This ultrahigh capacity retention at such high current densities is comparable among the reported studies. To fundamentally reveal the electrochemical mechanism, the bond valence method was employed to unravel the migration pathway of H + /Zn 2+ in VO2 (M). The H + diffusion pathway was fluent, while the Zn 2+ route had a narrow and blocked passage, which was consistent with the reversible deposition/dissolution of hydroxyzinc sulfate hydrate in the electrochemical process. The pseudocapacitive proton insertion mechanism can be a promising strategy to explore cathode materials for aqueous zinc ion batteries.